Validitas Tes Buatan Dosen (Survai pada Dosen di Fak. Tarbiyah IAIN Sulthan Thaha Saifuddin Jambi TA. 2010-2011) - Rizalman, Rizalman (Al-`Ulum, 2012)
The objective of the research is to study the relationships between Comprehension of Constructing Achievement Test, Perception of Evaluation System and Validity of Lecturers Constructed Test. The research was conducted at the Faculty of Education al IKIP Jakarta 1998/1999 with N - 41 lecturers by taking proportional random sampling technique. The research concluded that there are positive relationships between (1) comprehension of constructing achievement test (X1) and validity of lecturers constructed test (Y) with ry1 -0,49 and Y - 22,26 + 1,16X,, (2) perception of evaluation system (X2) and validity of lecturers constructed^ test (Y) with ry2 -0,34 and Y = 32,87 + 0,25X2. That is also positive relationships between those two independent variables with Two independent variables with dependent variables with R Y,? 0,56 and multiple regression ? = 13,00 + 103X1 + 0,18X2